Differential dynamics underlying the Gln27Glu population variant of the beta(2)-adrenergic receptor - Bhosale, Sumedha; Nikte, V. Siddhanta; Sengupta, Durba; Joshi, Manali (Journal of Membrane Biology, 2019)
The beta (2)-adrenergic receptor (beta (2)AR) is a membrane-bound G-protein-coupled receptor and an important drug target for asthma. Clinical studies report that the population variant Gln27Glu is associated with a differential response to common asthma drugs, such as albuterol, isoproterenol and terbutaline. Interestingly, the 27th amino acid is positioned on the N-terminal region that is the most flexible and consequently the least studied part of the receptor. In this study, we probe the molecular origin of the differential drug binding by performing structural modeling and simulations of the wild-type (Gln) and variant (Glu) receptors followed by ensemble docking with the ligands, albuterol, isoproterenol and terbutaline. In line with clinical studies, the ligands were observed to interact preferentially with the Glu variant. Our results indicate that the Glu residue at the 27th position perturbs the network of electrostatic interactions that connects the N-terminal region to the binding site in the wild-type receptor. As a result, the Glu variant is observed to bind better to the three ligands tested in this study. Our study provides a structural basis to explain the variable drug response associated with the 27th position polymorphism in the beta (2)AR and is a starting step to identify genotype-specific therapeutics.
Keywords: beta(2)-Adrenergic receptor; G-protein-coupled receptor; GPCR; molecular dynamics; Pharmacogenetics; SNP